Shopping mall attractiveness: consumers decision towards the selection of shopping mall / Zaimatul Awang - Awang, Zaimatul (2013)
Retail industry has been recognized as one of the industries that contributed to the rapid expansion of economic in Malaysia. As shopping malls is one of the sectors of the retail industry, it has played a prominent role in making Kuala Lumpur as number two of shopper paradise in Asia Pacific. Each year, the number of visitors has growth and in order to cater a large number of visitors, the development of the shopping mall in Klang Valley area have rapidly increased and it has lead to the oversupply situation. Besides, the management and the developer did not aware on the attributes and the attractiveness factor of the shopping mall that have attracted consumer to visit the shopping mall. Thus, this study aim at identifying the attributes of the shopping mall that gives effect most to the consumer decision making in choosing shopping mall. The objective of the study is focusing on these three attributes which are accessibility and convenient, entertainment and environment. By using self administered questionnaires that have been adapted and adopted by various previous researchers, it has been distributed to the consumer of top five regional shopping malls in Klang Valley. A total of two hundred and thirty questionnaires were obtained and have been analyzed using the SPSS version 20. A descriptive and inferential used to obtain the results. The finding shows that those three attractiveness factor have affected consumer decision making but as to compare between those three attributes, the convenience attributes have give the most influence and effect towards consumers’ decision. Further implication and recommendations has also been given.